A thermal microfluidic actuator based on a novel microheater. (1st March 2023) - Qaiser, Nadeem; Khan, Sherjeel M; Babatain, Wedyan; Nour, Maha; Joharji, Lana; Shaikh, Sohail F; Elatab, Nazek; Hussain, Muhammad Mustafa
Abstract: Microfluidic actuators based on thermally-induced actuation are gaining intense attraction due to their usage in disease diagnosis and drug release-related devices. These devices use a thermally-expandable polymer called Expancel that expands once its temperature exceeds a particular threshold value. Achieving such devices that are cost-effective and consume low input power is crucial for attaining efficacy. Therefore, the need for a low-energy consuming actuator necessitates the improved configurations of microheaters that provide the required heat. We report a novel topology of a copper-based microheater called square-wave meander, exhibiting a 44% higher output temperature, showing high actuation efficiency, as compared to the conventionally used meander design. The reason for increased temperature with low input energy is attributed to increased resistance by a jagged structure while maintaining the same surface area, i.e. without changing the effective thickness of the microheater. Numerical modeling demonstrates the comparison of temperature and electric potential contours for reported and conventionally used microheaters. We reveal the merit of the reported design by comparing the volumetric thermal strains for both designs. We experimentally demonstrate the increased expansion of 25% for the reported design at the same applied current of 200 mA and faster operation time. Later, we show the microfluidic actuator device integrated into the microheater and poly-dimethylsiloxane-Expancel, controlling the operation/actuation of a fluid through a microchannel. This work might improve the performance of the advanced microfluidic-based drug release and other fluid-based applications.